COMPARISON OF EFFECT OF LOW DOSE DEXMEDETOMIDINE INFUSION (0.2 VS 0.4 MCG/KG/HR) ON HEMODYNAMIC STRESS RESPONSE IN PATIENTS UNDERGOING LAPROSCOPIC CHOLECYSTECTOMY UNDER GENERAL ANESTHESIA AT TERTIARY CARE HOSPITAL KARACHI - Muhammad Moazzam Ali; Maria Hashmi; Hubba Ahmed; Hajra Zafar Siddiqui; Umama Masnoon; Atif Shafqat; Syed Farjad Sultan (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Dexmedetomidine, an α2-adrenergic receptor agonist, has gained prominence for its hemodynamic stabilizing properties in anesthesia. Its dose-dependent effects on reducing stress responses during laparoscopic surgeries remain underexplored. Objective: To compare the effects of low-dose dexmedetomidine infusion at 0.2 mcg/kg/h versus 0.4 mcg/kg/h on the hemodynamic stress response in patients undergoing laparoscopic cholecystectomy under general anesthesia. Study Design and Setting: This randomized controlled trial was conducted from November 2020 to March 2021 at the Department of Anesthesiology, Civil Hospital Karachi. Methodology: A total of 182 patients (91 per group) of ASA status ≤2, aged 20–60 years, were randomly assigned to receive dexmedetomidine infusions at 0.2 mcg/kg/h (Group A) or 0.4 mcg/kg/h (Group B). Hemodynamic parameters, including pulse rate (PR) and mean arterial pressure (MAP), were recorded at predefined intervals. Results: Group B demonstrated significantly lower pulse rates and mean arterial pressures compared to Group A at all measured time points. For example, at 1 minute post-intubation, the pulse rate was 96.57 ± 3.52 in Group A versus 86.98 ± 1.06 in Group B (p = 0.001). Similarly, MAP was 101.1 ± 9.54 mmHg in Group A versus 94.69 ± 1.58 mmHg in Group B (p = 0.001). These differences persisted post-stratification for variables such as age, gender, BMI, and surgical duration. Conclusion: A dexmedetomidine infusion at 0.4 mcg/kg/h is more effective in attenuating the hemodynamic stress response during laparoscopic cholecystectomy compared to 0.2 mcg/kg/h, with statistically significant reductions in pulse rate and mean arterial pressure.